Formulation and Evaluation of Spray Gel Fraction of Ethyl Acetate of Purslane Leaves (Portualaca Olercea.L) as an Anti-inflammatory in Wistar Rats - Yoni Nugrahaning Widhi; Arini Syarifah; Didik Setiawan (Proceedings Series on Health & Medical Sciences, 2026)
The Pharmacy Study Program is an academic program that prepares students to become pharmacists, focusing on the study of medications, their effects, and the safe and effective practice of dispensing them. This program includes courses in Pharmaceutical Sciences, where students learn about drug development, formulation, and delivery; Pharmacology, which studies how drugs interact with the body; Pharmacy Practice, training students in patient interactions, medication counseling, and pharmacy management; Clinical Pharmacy, where students work with healthcare teams to optimize medication therapy; and Pharmaceutical Chemistry, focusing on the chemical properties and synthesis of drugs. Upon graduation, typically with a Bachelor of Pharmacy or PharmD degree, students are qualified to work in hospitals, clinics, and community pharmacies, ensuring the safe and effective use of medications.